2005
DOI: 10.1016/j.ydbio.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the digestive system in zebrafish: III. Intestinal epithelium morphogenesis

Abstract: Recent analysis of a novel strain of transgenic zebrafish (gutGFP) has provided a detailed description of the early morphological events that occur during the development of the liver and pancreas. In this paper, we aim to complement these studies by providing an analysis of the morphological events that shape the zebrafish intestinal epithelium. One of our goals is to provide a framework for the future characterization of zebrafish mutant phenotypes in which intestinal epithelial morphogenesis has been disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
348
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(369 citation statements)
references
References 75 publications
18
348
1
2
Order By: Relevance
“…Thus this model may provide an appropriate platform to probe the intersection of metabolism and immune function using small molecules and genetics. However, it is known that the larval zebrafish gut undergoes significant morphological maturation after 3 dpf as the linear gut tube undergoes convolution and folding (Wallace and Pack, 2003;Ng et al, 2005). As such, it may not be appropriate to analyze inflammationdriven changes of intestinal differentiation within such a developmentally active system Noble et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus this model may provide an appropriate platform to probe the intersection of metabolism and immune function using small molecules and genetics. However, it is known that the larval zebrafish gut undergoes significant morphological maturation after 3 dpf as the linear gut tube undergoes convolution and folding (Wallace and Pack, 2003;Ng et al, 2005). As such, it may not be appropriate to analyze inflammationdriven changes of intestinal differentiation within such a developmentally active system Noble et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Larval zebrafish are experimentally accessible for the study of mucosal immunology because of their transparency and the production of large numbers of embryos. Research into zebrafish gastrointestinal function has identified many orthologous gene and signaling pathways necessary for digestive and mucosal immune function (Wallace and Pack, 2003;Ng et al, 2005;Bates et al, 2007;Flores et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The largest subgroups of well-differentiated BPNETs are typical carcinoids (TCs), while within the GI tract, the small intestine (SI) is the most common site [24] . With the interest of NKX2.2 functions, Ng et al first published the research that a transgenic zebrafish line with EGFP driven by the NKX2.2a locus identifies endocrine cells in the intestine [25] . Wang et al carried out a series of studies to ascertain the role of NKX2.2 in normal and neoplastic gut.…”
Section: Nkx22mentioning
confidence: 99%
“…[46][47][48] Zebrafish are a suitable natural host model for V. cholerae colonisation and transmission as their gastrointestinal development and physiology closely mimics that of mammalian organisms. 49 Additionally, ease of propagation and live imaging made them a good choice of host for our in vivo studies, in particular at this early . CC-BY 4.0 International license not peer-reviewed) is the author/funder.…”
Section: Cc-by 40 International License Not Peer-reviewed) Is the Aumentioning
confidence: 99%